Adductor canal block: Effect of volume of injectate on sciatic extension - Raddaoui, Khaireddine (Saudi J Anaesth, 2020)
CONTEXT: Spread of local anesthetic within adductor canal to peroneal and tibial nerves is described in literature. This spread could be volume-dependent. AIMS: In this study, we compared the diffusion of two volumes of 0.375% ropivacaine to popliteal fossa. SETTINGS AND DESIGN: This was a prospective, randomized controlled, single-blind study conducted in Kassab Orthopaedic Institute of Tunis for 1 year (2018). MATERIALS AND METHODS: A total of 42 patients, American Society of Anesthesiologists I/II scheduled for knee arthroscopy under spinal anesthesia scheduled to receive adductor canal block, were randomized into two groups: group N received 20 mL of ropivacaine 0.375% and group H received 40 mL. We evaluated sensory motor blocks of both peroneal and tibial nerves at 30 and 60 min. STATISTICAL ANALYSIS USED: Chi-square or Fisher's exact test was used to compare the number and percentage. P <0.05 was significant. RESULTS: At 60 min, complete sensory block of the peroneal nerve was obtained for 16 patients in group H versus 15 patients in group N with no statistically significant difference (P = 0.60). The difference was also not significant (P = 0.27) for the tibial nerve: 14 patients for group H versus 16 for group N. Motor blockade was rare in the two nerve territories. CONCLUSION: Spread of 0.375% ropivacaine to popliteal fossa resulted in high rate of complete sensory blockade of both peroneal and tibial nerves. Diffusion of local anesthetic was not volume-dependent.